Bribery Detection Strategy: A Conceptual Model - Briyan Efflin Syahputra; Junaidi; Anggit Esti Irawati (Universitas Teknologi Yogyakarta, 2022)
Bribery is a type of corruption with a high number of cases almost every year, including in Indonesia. This condition is getting worse because most bribery occurs in government circles. Therefore, finding an effective solution to detect bribery is the focus of many parties, especially the government. By seeing this solution in the future, the number of bribery cases can decrease significantly. This research aims to develop a holistic model that includes potential factors for detecting bribes. This research will use a literature review to obtain data. The results of this research indicate that three potential factors effectively detect bribery. The factors are forensic audit and internal audit, which are potentially effective methods to detect bribery. In addition, another factor is big data, which has the potential to increase the role of forensic audits and internal audits to detect bribery.